PERAN KULTUR DALAM PENELITIAN Punica granatum MENAIKKAN KADAR GLUTATHION PEROXYDASE PADA KULTUR HUVECs YANG DIPAPAR PLASMA PRE EKLAMPSI (article review) - Suhrawardi, Suhrawardi (Jurnal Cakrawala Ilmiah, 2025)
The HUVECs (Human Umbilical Vein Endothelial Cells) cell culture model was used in this study to investigate the effects of Punica granatum extract on Glutathione Peroxidase (GPx) levels under preeclampsy conditions. HUVECs endothelial cell culture is an appropriate choice because of its ability to replicate the conditions of endothelial dysfunction that occur in preeclampsia, which affects the blood vessels of pregnant women. The advantage of this in vitro model is its ability to isolate and manipulate specific factors involved in oxidative stress and vascular dysfunction without the variability derived from systemic factors in the human body. By using cell cultures of HUVECs, this study allowed researchers to monitor cell responses to preeclamptic plasma exposure and pomegranate extract treatment in a more controlled and scalable manner. The use of cell culture provides greater insight into the molecular mechanisms involved in endothelial cell damage in preeclampsia and the potential for natural material-based therapies. Although this study was limited to in vitro experiments, the results obtained demonstrate the importance of cell culture as a model that can accelerate the understanding and development of therapies for preeclampsia